The Reasons for the Absence of Aging Policies in Indonesian Universities: A Case Study of Two Fully Autonomous Public Universities - Ramadhan, Adityo Pratikno; Sibly, Suzyrman; Khelghat-Doost, Hamoon (Journal of Population and Social Studies [JPSS], 2022)
In 2019, more than 27% of academic staff at Indonesian public universities were over 60, suggesting the importance of clearly stated policies on aging in these institutions. However, an aging policy is still absent in public universities. Thus, the purpose of this study is to ascertain why Indonesian public universities lack a distinct policy for their older academic staff. An exploratory qualitative approach was employed in this study. Two fully autonomous and well-known public universities in Indonesia were chosen as case studies. The selected members of top management of these universities comprising the rector, vice-rectors, and directors were individually interviewed. The result of the study revealed that these institutions do not have a specified aging policy. The result also highlighted eight reasons why public universities do not have an aging policy in their institution. The study suggests further investigation of the reasons for the absence of aging policies in Indonesian universities are carried out using a large sample size within fully autonomous public universities, non-fully autonomous public universities, and private universities to delve deeper into the reasons for the absence of an aging policy.